Dynamic modeling and analysis of 3-RRCPR parallel pointing mechanism with clearance - Sun, Jing; Song, Jingwei; Wang, Yongjie (Transactions on Engineering and Technology Research, 2024)
In order to study the influence of kinematic pair clearance on the dynamic characteristics and pointing accuracy of 3-RRCPR parallel pointing mechanism, the dynamic model of spatial mechanism with three-dimensional revolute pair clearance is established. Firstly, the revolute pair mode considering three-dimensional clearance is established, and the normal and tangential contact force models between the kinematic pair elements are established based on Flores contact model and modified Coulomb friction model. Secondly, the dynamic model of parallel mechanism with clearance is established according to Lagrange multiplier method. Finally, the effects of different clearance sizes and loads on the dynamic characteristics and pointing accuracy of the mechanism are analyzed by numerical simulation. The results show that the increase of clearance size and load will reduce the pointing accuracy, and the decrease of clearance size and the increase of load will enhance the motion stability of the mechanism. Reasonable clearance and load matching is conducive to improving the accuracy of the mechanism. This study provides a theoretical basis for the study of the nonlinear dynamic characteristics and accuracy of the mechanism considering the clearance.